Biochemical Characterization And Analysis Of Moringa Oleifera Seeds On Mcf7 Cells - Ismail Abiola, Adebayo (2019)
In this study, the antioxidant activity of the plant seed and its antiproliferative effect against Michigan Cancer Foundation-7 (MCF7) breast cancer cells were investigated, and the underlying mechanisms of actions involved were unravelled using molecular biological methods such as 2-dimensional gel electrophoresis (2- DE), western blotting and reverse transcription polymerase chain reaction (RT-PCR). l,l-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis-3-ethylbenzthiazoline-6- sulphonic acid (ABTS) tests showed that all the extracts and fractions from the seeds have antioxidant capacities.